2003
DOI: 10.1002/rcm.970
|View full text |Cite
|
Sign up to set email alerts
|

Determination of α‐tocopherol in infant foods by liquid chromatography combined with atmospheric pressure chemical ionisation mass spectrometry

Abstract: A novel, sensitive and specific method for the quantification of alpha-tocopherol in two infant foods (milk and cereals) using liquid chromatography on-line with positive atmospheric pressure chemical ionisation mass spectrometry detection (LC/APCI-MS) has been developed. The samples were first saponified in order to eliminate fats and to transform tocopherol esters into free tocopherol, followed up by a liquid-liquid extraction of the analyte in petroleum benzine/diisopropyl ether (75:25, v/v) prior to inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
1
21
2
Order By: Relevance
“…In this case the closest match corresponds to C 29 H 49 O 2 , which is the formula for α ‐tocopherol. The clear and monoisotopically resolved spectrum obtained by ESI‐TOF contrasts with the spectrum obtained in previous methods employing either single14 or triple12,13 quadrupole mass spectrometers. In these methods, APCI+ MS/MS,12 APCI+ MS,14 and ES+ MS/MS13 produced a cluster of ions for α ‐tocopherol in the m/z range 423–432, the expected target protonated ion not being the predominant species.…”
Section: Resultscontrasting
confidence: 83%
See 3 more Smart Citations
“…In this case the closest match corresponds to C 29 H 49 O 2 , which is the formula for α ‐tocopherol. The clear and monoisotopically resolved spectrum obtained by ESI‐TOF contrasts with the spectrum obtained in previous methods employing either single14 or triple12,13 quadrupole mass spectrometers. In these methods, APCI+ MS/MS,12 APCI+ MS,14 and ES+ MS/MS13 produced a cluster of ions for α ‐tocopherol in the m/z range 423–432, the expected target protonated ion not being the predominant species.…”
Section: Resultscontrasting
confidence: 83%
“…The clear and monoisotopically resolved spectrum obtained by ESI‐TOF contrasts with the spectrum obtained in previous methods employing either single14 or triple12,13 quadrupole mass spectrometers. In these methods, APCI+ MS/MS,12 APCI+ MS,14 and ES+ MS/MS13 produced a cluster of ions for α ‐tocopherol in the m/z range 423–432, the expected target protonated ion not being the predominant species. The presence of these additional ions has been attributed both to the oxidation of α ‐tocopherol, and to the protonation followed by dehydrogenation of α ‐tocopherol, during ionisation12 and represents novel ionisation characteristics.…”
Section: Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…Thus, other detection methods were investigated, and it was found that the application of atmospheric pressure chemical ionization (APCI)-MS to the usual HPLC afforded a partial improvement to the problem [32]. Furthermore, the use of a shorter column (150 mm × 4.6 mm i.d.)…”
Section: Introductionmentioning
confidence: 97%